Association between vitamin D status and asymmetric dimethylarginine (ADMA) concentration in the Korean elderly population. (August 2017) - Choi, Hye Rin; Lee, Seung Won; Yeom, Hyungseon; Jeon, Da-Hye; Kim, Hyeon Chang; Youm, Yoosik
Highlights: In our sample of elderly Koreans, the serum level of vitamin D (25(OH)D) was significantly and negatively correlated with the asymmetric dimethylarginine (ADMA) concentration. Vitamin D deficiency was associated with higher concentrations of asymmetric dimethylarginine in both women and men. Vitamin D deficiency may be associated with endothelial dysfunction in the Korean elderly population. Abstract: Objectives: Vitamin D deficiency has been reported to be associated with the risk of cardiovascular disease. We investigated the relationship between vitamin D status and asymmetric dimethylarginine (ADMA) concentration, a marker of endothelial dysfunction, in the Korean elderly population. Study design: A cross-sectional study was conducted on 269 men and 382 women (mean age, 71.6 years) enrolled in the Korean Social Life, Health, and Aging Project (KSHAP), a population-based longitudinal study of health determinants in elderly Koreans. We stratified patients by vitamin D status into three groups according to serum 25-hydroxyvitamin D [25(OH)D] level: sufficient (≥30 ng/mL, n = 25), insufficient (10- < 30 ng/mL, n = 516), and deficient ( < 10 ng/mL, n = 110). To measure endothelial dysfunction, ADMA concentration was assayed by high-performance liquid chromatography. The association between 25(OH)D status and ADMA concentration was analyzed by multiple linear regression models. Results: The mean ADMA concentration was significantly higher in the insufficient 25(OH)D group (0.665 μmol/L, p = 0.001) and the deficient 25(OH)D group (0.734 μmol/L, p < 0.001) compared with the sufficient 25(OH)D group (0.589 μmol/L). Even after adjusting for sex, age, body mass index, blood pressure, diabetes mellitus, total and HDL cholesterol, estimated glomerular filtration rate (eGFR), smoking status, and drinking status, ADMA concentrations were higher in the insufficient group (β = 0.0742 μmol/L, p = 0.001) and the deficient group (β = 0.1417 μmol/L, p < 0.001) compared than in the sufficient group. In a sex-stratified analysis, 25(OH)D deficiency was associated with higher ADMA levels in both women (p < 0.001) and men (p = 0.007), while 25(OH)D deficiency was associated with higher ADMA levels in women (p < 0.001) but not in men (p = 0.631). Conclusion: Our findings suggest that low serum 25(OH)D level may be associated with endothelial dysfunction in elderly Korean people.